Photodetectors on the Basis of Porous Silicon - I.B. Olenych; L.S. Monastyrskii; B.S. Sokolovskii (Журнал нано- та електронної фізики)
The paper studies the electrical characteristics of photodiode structures porous silicon – silicon substrates modified with molecules of iodine. Changes the nature of current-voltage characteristics obtained structures with symmetrical for straightening result of adsorption of iodine are revealed. It is studied the spectral characteristics of photoresponse in the 450-1100 nm wavelength range, its temperature dependence in the 125-325 K range and energy characteristics of photovoltaic structures based on porous silicon. A possible mechanism of influence of iodine adsorption on the electrical and photoelectrical properties of the structures of porous silicon – silicon substrates is proposed. The results extend the perspectives of porous silicon in photoelectronics.